Moisture adsorption isotherms of amorphous cassava starch at different temperatures determined by a dynamic vapor sorption technique - Sandoval, A.; Barreiro, J.; Müller, A. (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2012)
Â Moisture adsorption isotherms of amorphous cassava starch were determined at temperatures of 5, 30 and 45°C using a dynamic vapour sorption technique (DVS). Thirteen relative humidity values were set in a range from 0 to 94.5% for each temperature. Type-II isotherms were obtained in all cases. The effect of increasing temperature on the whole water activity range of the adsorption isotherms showed a decrease in the equilibrium moisture content. The data did not display any isotherm cross-over with temperature at elevated water activities as previously reported for this product using thymol as an antimicrobial agent. Different isotherm models were used to describe the sorption behaviour of amorphous cassava starch. The modified GAB model exhibited the best statistical results. For the temperature range studied, the A, B, C and D parameters in this model ranged from 0.127-0.255 6.93-53.0, 0.493-0.0181 and 0.137-0.503, respectively. Monolayer water content ranged from 0.0547 to 0.0727 g.g”“1 of dry solids using the BET equation and 0.0433 to 0.0637 g.g”“1 of dry solids, when the GAB model was used. The net isosteric heat of sorption obtained ranged from 0.8 to 6.9 kJ.mol”“1 in a moisture content range of 10-27 g.100 g”“1 of dry solids. Contrary to previous research works no antimicrobial agents that could alter isotherms were used in isotherm determinations. Therefore, moisture adsorption data obtained in this work using the DVS technique is more accurate than those previously reported for amorphous cassava starch using the traditional static gravimetric technique.